Motivations for suicide attempts and risk factors among youths in Western Iran: A cross‐sectional study - Fatemeh Darabi; Arash Ziapour; Hassan Ahmadinia (Health Science Reports)
Abstract Background and Aims Suicide attempts are a fundamental problem in health care systems and are known for their complex and multifaceted nature. This study aimed to explore the reasons for suicide attempts and to identify associated factors in western Iran. Methods In Asadabad, western Iran, a cross‐sectional study was carried out between April 2020 and March 2021. A nonrandom sampling method was used to select 110 participants, ages 15–35. Structured questionnaires such as the Beck Anxiety Inventory (BAI), the Beck Depression Inventory (BDI‐II), and the Suicide Motivation Scale (IMSA) were used to gather the data. Multiple linear regression, one‐way analysis of variance, Pearson's correlation coefficient, and independent t tests were all used in the data analysis. Results The majority of participants (59.1%) were female, with a mean age of 25.78 years. The most common reason for suicide attempts (43.6%) was family issues, and the most popular means (66.4%) were pills and medication. Eighty‐nine percent of participants had symptoms of depression. The mean scores were calculated for motivation for suicide attempts (32.46 ± 16.11), depression (34.60 ± 20.50), and anxiety (34.14 ± 15.69). The analysis showed that the motivation for suicide attempts and anxiety was greater in single persons than in married and divorced persons (p < 0.05). Motivation for suicide attempts was also greater in low‐ to middle‐income individuals with a history of divorce (p < 0.05). The multiple regression model showed that anxiety, sex, education, and medical history significantly influenced the motivation for suicide attempts (p < 0.001). Conclusion The results showed that a wide range of social, economic, and cultural factors and psychiatric disorders, including anxiety and depression, are involved in suicide attempts. This study aimed to design interventions and strategies to prioritize mental health, improve life skills to control stressful events, and focus on high‐risk groups (women, married people, people with low education levels, and those with a history of physical and mental illnesses) for suicide prevention in health promotion programs.